Synthesis, structure and magnetic phase transitions of the manganese succinate hybrid framework, MN(C4H4O4). - Saines, P; Melot, B; Seshadri, R; Cheetham, A (2010)
An anhydrous manganese succinate, Mn(C(4)H(4)O(4)), has been synthesised hydrothermally and studied by single-crystal X-ray diffraction. It adopts a succinate pillared structure in which layers of corner-sharing MnO(6) octahedra alternate with sheets that contain chains of edge-sharing octahedra. This unique 3D framework structure contains highly distorted MnO(6) octahedra, which are made possible by the lack of ligand field stabilisation energy for the high-spin Mn(2+) ion. Attempts to dope the structure with other divalent transition-metal ions were accordingly unsuccessful. Magnetic susceptibility and heat capacity measurements indicate that Mn(C(4)H(4)O(4)) undergoes antiferromagnetic ordering below 12 K, with a second antiferromagnetic transition at approximately 6 K. These two antiferromagnetic phases undergo further transitions in applied fields, underlining the subtle magnetic behaviour that is possible in inorganic-organic frameworks of this structural complexity.